Knowledge of ecological concepts, environmental concern, and ecological behavior: A multiple correlation analysis - Dwi Angelita; Mieke Miarsyah; Ratna Komala (University of Muhammadiyah Malang, 2023)
Environmental problems are a concern of society. Solving environmental problems requires knowledge of ecological concepts, environmental awareness, and students' ecological behavior. The research aims to determine the relationship between ecological concept knowledge and environmental concern with students' ecological behavior. The research method uses a descriptive method with a cross-sectional survey technique on 180 participants at SMA Negeri 1 Sungailiat, Bangka Regency. Statistical data analysis using regression analysis and multiple correlation. Based on the prerequisite test, it was obtained that the data were normally distributed, the data was homogeneous, there were no symptoms of multicollinearity, heteroscedasticity, or autocorrelation. The results showed a multiple correlation coefficient of r = 0.776 in the strong category. The conclusion of the study is that there is a positive relationship between knowledge of ecological concepts and environmental awareness together with ecological behavior. Achievement of high student ecological behavior requires knowledge of ecological concepts and concern for the good environment of students.